2019
DOI: 10.1002/cssc.201901409
|View full text |Cite
|
Sign up to set email alerts
|

Lignin@Nafion Membranes Forming Zn Solid–Electrolyte Interfaces Enhance the Cycle Life for Rechargeable Zinc‐Ion Batteries

Abstract: Zn solid-electrolyte interfaces enhance the cycle life for rechargeable zinc-ion batteries.ChemSusChem, 12(21), 4889-4900, which has been published in final form at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 71 publications
3
112
1
Order By: Relevance
“…As displayed in Figure S16 in the Supporting Information, the initial morphology of Zn foil showed a flat planar structure, and there was some array structure on the Zn anode surface after cycling, which was the Zn dendrites and zinc sulfate hydroxide as mentioned in previous papers. [42][43][44][45] In this study, crystal water molecules and defects are introduced into the VO 2 tunnel structure simultaneously. The lattice defects break the strong electrostatic interaction between ion and host structure, offering rapid ion diffusion pathway.…”
mentioning
confidence: 99%
“…As displayed in Figure S16 in the Supporting Information, the initial morphology of Zn foil showed a flat planar structure, and there was some array structure on the Zn anode surface after cycling, which was the Zn dendrites and zinc sulfate hydroxide as mentioned in previous papers. [42][43][44][45] In this study, crystal water molecules and defects are introduced into the VO 2 tunnel structure simultaneously. The lattice defects break the strong electrostatic interaction between ion and host structure, offering rapid ion diffusion pathway.…”
mentioning
confidence: 99%
“…Advanced separators were designed to uniform Zn ion distribution, Liu et al proposed cross‐linked polyacrylonitrile (PAN)‐based cation exchange membrane (PAN‐S membrane) by employing Li 2 S 3 to react with PAN for high cation transport and homogeneous ionic flux distribution (Figure 7B) comparing to the nonwoven mat separator (Figure 7A). 79 Srinivasan et al reported a Nafion‐based separator with the interaction of Zn 2+ ‐SO 3 − achieving a dense and parallel surface texture 80 . The developing new separator system should consider the fabrication costs and mass production capability.…”
Section: Strategies Toward Dendrite Free the Zn Anodementioning
confidence: 99%
“…However, instable solid electrolyte interphase (SEI) as well as the resultant Li dendrite growth seriously cause safety concerns, once Li metal is implemented as an anode in a battery . In the view of being able to manipulate the mechanical properties by macromolecular chains as well as regulate Li ion flux and distribution by lithiophilic functional groups, biomass materials (eg, cellulose, starch, protein, lignin, chitin, polysaccharide) have been integrated into artificial SEI protective films for restraining Li plating and stripping to suppress the dendrite propagation . Recently, a natural agarose biopolymer film (AG) was reported as an enabling SEI protective layer.…”
Section: Natural Primordial Biological Polymersmentioning
confidence: 99%
“…74 In the view of being able to manipulate the mechanical properties by macromolecular chains as well as regulate Li ion flux and distribution by lithiophilic functional groups, biomass materials (eg, cellulose, starch, protein, lignin, chitin, polysaccharide) have been integrated into artificial SEI protective films for restraining Li plating and stripping to suppress the dendrite propagation. [75][76][77][78][79] Recently, a natural agarose biopolymer film (AG) was reported as an enabling SEI protective layer. The assembled Li-Cu half cell with AG protective layer displayed higher Coulombic efficiency of 98% even after 100 cycles, much better than that with bare Cu foils (< 40% after 50 cycles), indicative of the excellent structure stability of bio-based AG films against Li metal anode.…”
Section: Artificial Solid Electrolyte Interphase Layersmentioning
confidence: 99%